Verification of the knowledge of professionals regarding the FAST HUG mnemonic in the intensive care unit of the hospital in northern Brazil (Research, Society and Development, 2021)
This study aims to verify the knowledge of SUS health professionals, physicians, nurses and physiotherapists, who work in the Intensive Care Unit of a public hospital in northern Brazil, about the mnemonic FAST HUG. A cross-sectional and descriptive study was carried out, with qualitative and quantitative assessment, using a probabilistic sample. Data collection was performed through an online questionnaire with objective questions approved by the Ethics and Research Committee - CEP. Of the 50 ICU professionals contacted, only 25 were willing to respond to the consultation. Of these, 52% said they knew about the FAST HUG checklist. The best time to apply the protocol proved to be during the Rounds. Other relevant information found showed that 40% of professionals had difficulties in applying the checklist items, evidencing the need for training to align ideas and conduct the work. The institution of Rounds in the ICUs proves to be an essential utility for the application of the mnemonic FAST HUG.